Adverse Effects of Vemurafenib on Skin Integrity: Hyperkeratosis and Skin Cancer Initiation Due to Altered MEK/ERK-Signaling and MMP Activity - Tham, Marius; Stark, Hans-Jürgen; Jauch, Anna; Harwood, Catherine; Pavez Lorie, Elizabeth; Boukamp, Petra (Frontiers in Oncology, 2022)
The BRAF inhibitor Vemurafenib, approved for treating patients with BRAF V600E-mutant and unresectable or metastatic melanomas, rapidly induces cutaneous adverse events, including hyperkeratotic skin lesions and cutaneous squamous cell carcinomas (cSCC). To determine, how Vemurafenib would provoke these adverse events, we utilized long-term in vitro- skin equivalents (SEs) comprising epidermal keratinocytes and dermal fibroblasts in their physiological environment. We inserted keratinocytes with different genetic background (normal keratinocytes: NHEK, HaCaT (p53/mut), and HrasA5 (p53/mut+Hras/mut)) to analyze effects depending on the stage of carcinogenesis. We now show that Vemurafenib activates RAF-MEK-ERK signaling in both, keratinocytes, and fibroblasts in vitro and in the in vivo-like SEs. As consequence, Vemurafenib does not provide a growth advantage, but leads to a differentiation phenotype, causing accelerated differentiation and hyperkeratosis in the NHEK and normalized stratification and cornification in the transformed keratinocytes. Although all keratinocytes responded very similarly to Vemurafenib in their expression profile, particularly with a significant induction of MMP1 and MMP3, only the HrasA5 cells revealed a Vemurafenib-dependent pathophysiological shift to tumor progression, i.e. the initiation of invasive growth. This was shown by increased proteolytic activity allowing for penetration of the basement membrane and invasion into the disrupted underlying matrix. Blocking MMP activity, by the addition of Ilomastat, prevented invasion with all corresponding degradative activities, thus substantiating that the RAS-RAF-MEK-ERK / MMP axis is the most important molecular basis for the rapid switch towards tumorigenic conversion of the HrasA5 keratinocytes upon Vemurafenib treatment. Finally, co-treatment with Vemurafenib and the MEK inhibitor Cobimetinib prevented RAF-MEK-ERK hyperactivation and with that abolished both, the epidermal differentiation and the tumor invasion phenotype. This suggests that both cutaneous adverse events are under direct control of Vemurafenib-dependent RAF-MEK-ERK hyperactivation and confirms the dependence on preexisting genetic alterations of the skin keratinocytes that determine the basis towards induction of tumorigenic progression.